E-service quality model for assessing customer satisfaction of mobile banking application - Owuamanam, Jude Ndubuisi (2021)
The increasing growth of mobile device users, as well as the reduction in mobile data charges, have given way for the provision of mobile banking services. Banks are now extending their services from the traditional face-to-face banking interactions to a self-service system. Although mobile banking has grown exponentially, many users are not confident to transact using their phones due to the low e-service quality of mobile banking. To address the issue, this study proposes an enhanced model for assessing the e-service quality of mobile banking while examining the relationship between such e-service dimensions and customer satisfaction. To propose this model, MAPPSQL dimensions was adopted and was further extended by speed recovery and security from E-S-Qual dimensions. The primary data obtained from users of the mobile banking service in Nigeria were measured and analysed. A total number of 156 responses were obtained and analysed using structural equation modelling (SEM) of smart partial least square 2 (SmartPLS 2) software. Hypothesis tests were conducted to determine the relationship between the identified dimensions (i.e., app design, functionality, customization, assurance, fulfilment, service recovery, speed efficiency, and security) and customer satisfaction. The results show that app design, fulfilment and security are positively significant to customer satisfaction while functionality, customization, assurance, service recovery and speed efficiency are not significant to customers satisfaction. The results reveal that service providers should focus more on the dimensions of app design, fulfilment and security because these dimensions are vital indicators of customer satisfaction in mobile banking. The findings in this study will provide guidance and useful information to service providers on how the e-service quality of mobile banking systems can be improved.